2018
DOI: 10.1101/456574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complementary networks of cortical somatostatin interneurons enforce layer specific control

Abstract: The connectivity patterns of excitatory and inhibitory microcircuits are fundamental to computation in the neocortex. Highly specific excitatory projections form a stereotyped microcircuit linking the six cortical layers, but it is unclear whether inhibitory circuits are structured according to a similar layer-based logic or instead wire up non-selectively across the different layers. Understanding principles of inhibitory wiring is critical, since they constrain the computational operations that cortical inhi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 133 publications
(182 reference statements)
9
55
0
Order By: Relevance
“…The sixth met-type mapped to Sst Hpse Cbln4 and was found in L4 and upper L5; it strongly innervated L4 (with a less dominant projection to L1), and exhibited distinct electrophysiological properties including lower AP thresholds, less hyperpolarization-evoked sag, and more transient or irregular firing patterns. This met-type aligns with L5 Non-Martinotti cells in somatosensory cortex (Naka et al, 2019) that have distinct connectivity profiles compared to Martinotti neurons, though in visual cortex these neurons have much more L1 axon. The seventh met-type was composed of cells mapping to the Sst Crhr2 Efemp1, Sst Crh 4930553C11Rik, and Sst Esm1 t-types, was found in deep L5 and L6, and primarily innervated those layers with relatively few axonal projections to L1.…”
Section: Electrophysiologysupporting
confidence: 62%
See 1 more Smart Citation
“…The sixth met-type mapped to Sst Hpse Cbln4 and was found in L4 and upper L5; it strongly innervated L4 (with a less dominant projection to L1), and exhibited distinct electrophysiological properties including lower AP thresholds, less hyperpolarization-evoked sag, and more transient or irregular firing patterns. This met-type aligns with L5 Non-Martinotti cells in somatosensory cortex (Naka et al, 2019) that have distinct connectivity profiles compared to Martinotti neurons, though in visual cortex these neurons have much more L1 axon. The seventh met-type was composed of cells mapping to the Sst Crhr2 Efemp1, Sst Crh 4930553C11Rik, and Sst Esm1 t-types, was found in deep L5 and L6, and primarily innervated those layers with relatively few axonal projections to L1.…”
Section: Electrophysiologysupporting
confidence: 62%
“…The axons of neurons mapping to the Sst Hpse Cbln4 t-type -one of two major Sst t-types found in L4 -innvervate L1 and, to a greater degree, L4. A dominant L4 projection appears to be a common feature of Sst Hpse Cbln4 neurons across cortical areas (Naka et al, 2019). These results reveal that Sst neurons highly respect laminar boundaries across cortex, they have clear laminar innervation preferences that differ based on their met-type and/or laminar position, and that their dominant laminar target may be a more reliable feature for distinguishing among Sst neurons than the presence or absence of axon in layer 1.…”
Section: Discussionmentioning
confidence: 67%
“…The Sst family is known to be transcriptomically and phenotypically (Muñoz et al, 2017;Nigro et al, 2018;Naka et al, 2019) diverse in L5. Here we also found that electrophysiological properties varied con- Figure 1, colored by the membrane time constant.…”
Section: Continuous Phenotypic Variation Within Transcriptomic Familiesmentioning
confidence: 99%
“…Such horizontal inhibition from somatostatin (Sst) interneurons shapes the receptive field properties of nearby pyramidal neurons in L2/3 of mouse visual cortex . Several patterns of vertical inhibition (mediated by translaminar inhibitory connections) have been described for Sst-interneurons (Kapfer et al, 2007;Silberberg and Markram, 2007;Jiang et al, 2015;Anastasiades et al, 2016;Naka et al, 2019) as well as parvalbumin-interneurons (Olsen et al, 2012;Bortone et al, 2014). Furthermore, subtypes of Sst-interneurons may be differentially integrated into distinct layer-specific subnetworks (Muñoz et al, 2017;Naka et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several patterns of vertical inhibition (mediated by translaminar inhibitory connections) have been described for Sst-interneurons (Kapfer et al, 2007;Silberberg and Markram, 2007;Jiang et al, 2015;Anastasiades et al, 2016;Naka et al, 2019) as well as parvalbumin-interneurons (Olsen et al, 2012;Bortone et al, 2014). Furthermore, subtypes of Sst-interneurons may be differentially integrated into distinct layer-specific subnetworks (Muñoz et al, 2017;Naka et al, 2019). Although intra-and inter-laminar inhibitory inputs to L2/3 of V1 have been compared via one-photon photostimulation activation of GABAergic interneurons via either caged-glutamate (Xu et al, 2016) or channelrhodopsin-2 expression (Kätzel et al, 2011), potentially unique roles of subsets of GABAergic interneurons may be revealed by photostimulation techniques with increased genetic and spatial specificity.…”
Section: Introductionmentioning
confidence: 99%